Creativity as connectivity: a rhizome model of creativity. (24th February 2004) - Styhre, Alexander; Sundgren, Mats
The knowledge-management literature has been weak on theorising the notion of creativity. This paper is an attempt to conceptualise creativity as the series of connections in what French philosopher Gilles Deleuze calls a rhizome; a horizontal network structure wherein all nodes can be connected to one another. This argument is illustrated by the new drug development activities in the pharmaceutical industry. New drugs are developed in four major phases: Discovery (Phase 0) and Development (Phases 1, 2 and 3). In the earlier phases of Discovery and Development, pharmaceutical researchers make connections between various entities and events in order to produce a new candidate drug. All these connections are made in a single plane producing lines of thought that eventually enable the new drug to be registered. The rhizome model of creativity helps to ground the notion of creativity in a coherent ontological and epistemological model and to demystify creative processes. Thus the rhizome is a viable analytical instrument for creativity studies.